Brunei Darussalam : Recent Economic Developments. (IMF Staff Country Reports; Country Report, 1999)
This paper describes economic developments in Brunei Darussalam during 1997-98. In 1997, the economy grew by 4 percent led by strong construction and services activities, while average inflation declined to less than 2 percent. Current expenditures were contained, and a recovery in capital expenditures was financed by larger transfers from the Brunei Investment Agency. In 1998, the Brunei economy was adversely affected by the large decline in world price of crude oil, the collapse of a large domestic private company, and the impact of the Asian crisis.